2022
DOI: 10.1038/s41419-022-04875-w
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow mesenchymal stem cell-derived extracellular vesicles containing miR-181d protect rats against renal fibrosis by inhibiting KLF6 and the NF-κB signaling pathway

Abstract: Recent studies have investigated the ability of extracellular vesicles (EVs) in regulating neighboring cells by transferring signaling molecules, such as microRNAs (miRs) in renal fibrosis. EVs released by bone marrow mesenchymal stem cells (BMSCs) contain miR-181d, which may represent a potential therapy for renal fibrosis. miR-181d has been speculated to regulate Krüppel-like factor 6 (KLF6), which activates the nuclear factor-kappa B (NF-κB) signaling pathway. Luciferase assays were performed to confirm the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 39 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…Nevertheless it has been shown that MSC-EVs could directly have an anti-fibrotic effects in more organs. For example, Wang et al [ 47 ]have demonstrated that Bone marrow mesenchymal stem cell-derived extracellular vesicles containing miR-181d protect rats against renal fibrosis by inhibiting KLF6 and the NF-κB signaling pathway. Another previous study also reported that Human bone marrow mesenchymal stem cell-derived extracellular vesicles inhibit shoulder stiffness via let-7a/Tgfbr1 axis[ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless it has been shown that MSC-EVs could directly have an anti-fibrotic effects in more organs. For example, Wang et al [ 47 ]have demonstrated that Bone marrow mesenchymal stem cell-derived extracellular vesicles containing miR-181d protect rats against renal fibrosis by inhibiting KLF6 and the NF-κB signaling pathway. Another previous study also reported that Human bone marrow mesenchymal stem cell-derived extracellular vesicles inhibit shoulder stiffness via let-7a/Tgfbr1 axis[ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The left anterior descending coronary artery was identified and ligated 1.5 mm below the left atrium auricula. Successful MI was verified via epicardial blanching, and then 50 uL M-EVs or N-EVs (2 × 10 9 particles [52]) were divided into 4 equal portions and injected in the border zone of infarction area 30 min after ligation [47]. Post-operative analgesia was given as required (Carprofen, 10 mg/kg) to ensure that they did not experience any type pain.…”
Section: Rat MI Model and Assessment Of Heart Functionsmentioning
confidence: 99%
“…EVs derived from 2D cultured human bone marrow MSCs (hBMMSCs) were able to modulate brain immune responses induced by focal brain injury and reduce neuroinflammation [ 63 ]. Another study showed that human bone marrow MSC-derived EVs (hBMMSC-EVs) were efficacious in mitigating the progression of unilateral ureteral obstruction-induced renal fibrosis in rats, displaying an anti-fibrosis effect [ 64 ]. In addition, in a glutamate-induced rat retinal injury model, adipose MSC-derived EVs were shown to reduce retinal excitotoxicity and markedly improve the morphological and functional abnormalities of the inner retinal layer [ 65 ].…”
Section: Clinical Studies Of Stem Cell-derived Evsmentioning
confidence: 99%
“…EVs derived from planar 2D cultured BMMSCs have been shown to be effective in injury repair and regeneration, promotion of osteogenic differentiation, and anti-cancer activities [ 63 , 64 , 150 157 ]. However, researchers have found that EVs derived from 3D cultured BMMSCs were superior to 2D-EVs in promoting wound healing and angiogenesis.…”
Section: Current Applications Of Evs Derived From 3d Cultured Scsmentioning
confidence: 99%
“…In a few previous studies about EVs in kidney-related disease ( Pisitkun et al, 2004 ; Zhou et al, 2006a ; Bruno et al, 2009 ; Gonzales et al, 2009 ; Miranda et al, 2010 ; van Balkom et al, 2011 ; Alvarez et al, 2012 ; Merino et al, 2014 ; Fais et al, 2016 ), it was shown that EVs are endogenous or natural membranous nanoparticles that play important roles in essentially all organisms; were used as drug carriers in nanomedicine; and were found to play important roles in the diagnosis, treatment, and prognosis of kidney-related diseases ( Kalluri and LeBleu, 2020 ; Lu and Huang, 2020 ; Fan et al, 2022 ; Tang et al, 2022 ; Yang et al, 2022 ). Recently, there have been increasing developments on EVs for the detection and treatment of more different types of kidney diseases, including CKD ( Sun et al, 2019 ; Tang et al, 2020a ; Grange et al, 2020 ; Jin et al, 2021 ; Grange and Bussolati, 2022 ; Tang et al, 2022 ; Wang et al, 2022 ), AKI ( Sun et al, 2019 ; Tang et al, 2020a ; Xie et al, 2020 ; Jin et al, 2021 ; Kraińska et al, 2021 ; Grange and Bussolati, 2022 ; Tang et al, 2022 ), lupus nephritis ( Thongboonkerd, 2019 ; Garcia-Vives et al, 2020 ; Xie et al, 2020 ; van Zonneveld et al, 2021 ; Grange and Bussolati, 2022 ), kidney-related inflammation ( Sun et al, 2019 ; Thongboonkerd, 2019 ; Tang et al, 2020a ; Tang et al, 2020b ; van Zonneveld et al, 2021 ), glomerular-related disorders ( Thongboonkerd, 2019 ; Jin et al, 2021 ; Grange and Bussolati, 2022 ), transplantation ( Thongboonkerd, 2019 ; Grange and Bussolati, 2022 ), diabetes ( Thongboonkerd, 2019 ; Grange and Bussolati, 2022 ; Tang et al, 2022 ), cancer ( Thongboonkerd, 2019 ; van Zonneveld et al, 2021 ), fibrosis ( Thongboonkerd, 2019 ;...…”
Section: Introductionmentioning
confidence: 99%